THE REATIONSHIP OF MOMPRENEUR OPTIMISM AS PERFORMANCE IMPROVEMENT THROUGH SUPPORT OF INNOVATION AND MARKET ORIENTATION - Aisyah; Fivi Rahmatus Sofiyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The Covid-19 pandemic has changed the way of ife in work, schoo, sociaizing, and any activities carried out outside the housethat wi contact other peope. Especiay with the impementation of partia ockdown, PSBB, work from home (WFH), stay at home, isoation, socia distancing, and even regiona quarantine. Where a peope are advised not to do activities outside their house, incuding work. The habit of working ike this wi have a positive impact. For exampe, if women experience a chaenging task, they will become more independent and robust. Nowadays,married women can not ony act as housewives but aso have gender equaity to do business from their homes to support their needs. Being a mompreneur has many advantages, one of which is the fexibe working hoursadapted to your family. Mompreneurs can sti do househod chores that go hand in hand with running their business.This study aimed to anayze the effect of sef-efficacy and sef-esteem on mompreneur performance through market orientation and innovation orientation. This study used accidenta samping with a tota sampe of 215 mompreneurs in the city of Medan. The data anaysis method used partia east squares anaysis with SmartPS software. The resuts showed that directy sef-efficacy, sef-esteem, market orientation, and innovation orientation had a positive and significant effect on mompreneur performance, and indirecty, it was known that sef-efficacy and sef-esteem had a positive and significant impact on mompreneur performance through market orientation and innovation orientation.